THE EFFECT OF SNAKE AND LADDER GAME TOWARDS STUDENTS’ ENGLISH LEARNING ACHIEVEMENT AT THE SIXTH GRADE STUDENTS OF ELEMENTARY SCHOOL IN SUKASADA IN ACADEMIC YEAR 2015/2016 - ., I Putu Wana Prasthadi; ., Dra.Ni Made Ratminingsih, MA; ., Made Hery Santoso, S.Pd, M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Penelitian ini bertujuan untuk menginvestigasi pengaruh permainan ular tangga terhadap hasil belajar bahasa Inggris siswa Sekolah Dasar kelas 6 di Sukasada pada tahun akademik 2015/2016. Desain penelitian ini adalah posttest only control group design. Populasi yang digunakan dalam penelitian ini adalah semua siswa kelas 6 di Kelurahan Sukasada. Sample diambil dengan menggunakan teknik Cluster Randon Sampling. Dua kelompok diambil sebagai sample penelitiian, kemudian dua sample dipilih menjadi kelompok eksperimen dan kontrol. Kelompok eksperimen diajarkan dengan menggunakan permainan ular tangga dan kelompok kontrol diajar dengan ceramah. Pada akhir pengajaran, siswa diberikan posttest. Hasil dari posttest ini dianalisis menggunakan deskriptif dan inferensial statistik. Hasil penelitian menunjukkan, nilai rata-rata siswa kelompok eksperimen lebih tinggi dari kelompok kontrol (79.10 > 61.65). Disamping itu,dari uji T, diperoleh nilai thitung = 5.487, yang mana lebih tinggi dari nilai ttabel = 2.030. Berdasarkan hasil tersebut, dapat disimpulkan bahwa ada pengaruh yang signifikan dari penggunaan permainan ular tangga terhadap hasil belajar bahasa Inggris siswa. Dengan demikian, permainan ular tangga adalah media pembelajaran yang baik untuk mengajar bahasa Inggris.Kata Kunci : permainan ular tangga, young learners, hasil belajar bahasa Inggris This study aimed at investigating the effect of Snake and Ladder towards students’ English learning achievement at the sixth grade students of elementary school in Sukasada in academic year 2015/2016. The design of the study was posttest only control group design. The population of this study was all the sixth grade students in Sukasada, Sukasada subdistrict, Buleleng Regency in academic year 2015/2016. Two groups were taken by using cluster random sampling technique as the samples of the study. The samples were chosen to be experimental and control group by using lottery. The students in the experimental group were taught by using Snake and Ladder game, while those in the control were taught by lecturing. At the end of the treatment, both groups were given a posttest. The data obtained in this study were analyzed by using descriptive and inferential statistics. The result of the study showed that the students in experimental group obtained better score than those in control group, which was proven by the mean score (79.10 > 61.65). Moreover, the result of independent sample t-test showed that the value of t observed was 5.487 which was higher than t critical value (2.030). It was proven that there was significant effect of using Snake and Ladder game towards students’ English learning achievement. Based on that, Snake and Ladder game is considered as a good media for teaching English for young learners.keyword : Snake and Ladder game, young learners, English learning achievement